Optimasi Jumlah dan Lokasi Tempat Perhentian Bus (TPB) Trans Padang Koridor V dengan Model Set Covering Problem - Sari, Engla Diva; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2023)
Trans Padang is a bus managed by the Padang City government since 2014. One of the corridors on the Trans Padang bus is corridor V uses a Bus Stop. However, the existence of TPB Trans Padang corridor V is not optimal. The purpose of this research is to determine the optimal number and location of TPB is to use The Set Covering Problem Model. The data sought is the location where there may be crowds. Then the data is validated using the Cochran Q-Test so that the data becomes a point of request. Next, a set of cover problem will be made and will be solved with the Enumerasi Implicit method. The results of processing using the Enumersi Implicit method obtained that the optimal TPB was 26 TPB, with the addition of TPB locations in 10 locations, is RSU Bunda BMC Padang, Simpang Sawahan, Simpang Lubeg, Erick Minimarket, Pitameh Garden, Budiman Cengkeh, Hoya Cengkeh, MR DIY Banda Buek, Dalas Swalayan, dan MTS AL FATAH.